RELATIONSHIP BETWEEN ARGYROPHILIC PROTEINS OF NUCLEOLAR ORGANIZER REGIONS AND ANTIGEN KI-67 WITH CLINICAL AND MORPHOLOGICAL PARAMETERS AND SURVIVAL IN LUNG ADENOCARCINOMA - D. S. Kobyakov; V. V. Klimachev; A. M. Avdalyan; I. P. Bobrov; A. F. Lazarev (Сибирский онкологический журнал)
Argyrophilic proteins associated with nucleolar organizer regions (Ag-NOR proteins) and Ki-67 antigen were investigated in patients with lung adenocarcinoma. Tumors with low and high content of Ag-NOR proteins and proliferation index (PI) Ki-67 were determined. The relationship between the Ag-NOR content and T and N parameters, tumor size of 3 cm or more and stage of the disease was found. High survival rates in patients with lung adenocarcinoma were associated with the low content of Ag-NOR proteins and PI Ki-67 and low survival rates were related to the high content of Ag-NOR proteins and PI Ki-67. The intermediate survival rates were related to the opposite values of the content of Ag-NOR proteins and PI Ki-67. The tumor size, N parameter and the content of Ag-NOR proteins had an independent effect on survival of patients. Survival was related to the size of the tumor in lung cancer patients having no lymph node involvement and it was related to the content of Ag-NOR proteins in cases with the presence of metastases. Mutual study of Ag-NOR proteins and antigen Ki-67 has differential diagnostic and prognostic value in lung adenocarcinoma.